2007
DOI: 10.1002/adfm.200600917
|View full text |Cite
|
Sign up to set email alerts
|

Organic Thin‐Film Photovoltaic Cells Based on Oligothiophenes with Reduced Bandgap

Abstract: The best polymeric solar cells reported so far are based on a so‐called bulk heterojunction of a polythiophene as donor and a soluble fullerene derivative as acceptor. However, these cells still suffer from an unsatisfying photovoltage, typically below 0.7 V. Here, we show that we can achieve higher photovoltages using a new terthiophene end‐capped with electron withdrawing dicyanovinyl groups (DCV3T) that increase both the ionization energy and even more strongly the electron affinity of the compound. The new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
132
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 28 publications
7
132
0
1
Order By: Relevance
“…Related work in our group has shown that such blend layers can be used in flat heterojunction solar cells where the triplet excitons are separated at the interface to a donor material into holes on the donor and electrons on C 60. [8] We therefore believe that the concept is of general significance and might open a route to highly efficient solar cells, if similar blend systems with high triplet diffusion lengths at room temperature are found.…”
Section: Introductionmentioning
confidence: 99%
“…Related work in our group has shown that such blend layers can be used in flat heterojunction solar cells where the triplet excitons are separated at the interface to a donor material into holes on the donor and electrons on C 60. [8] We therefore believe that the concept is of general significance and might open a route to highly efficient solar cells, if similar blend systems with high triplet diffusion lengths at room temperature are found.…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent years, solution processable BHJ organic solar cells based on conjugated small molecules and fullerenes have been extensively investigated. [5][6][7][8][9][10][11] Solution processable small molecules have numerous merits, such as, high chemical stability, high carrier mobility, well defined structures, easy synthesis and purification, intrinsically monodisperse, and few deep electron traps in solid films. [12][13][14] Oligothiophenes possess the above advantages, which makes them promising donors for solution processed BHJ solar cells when blend them with PCBM.…”
mentioning
confidence: 99%
“…The absorption spectrum of DCN7T film spreads from 400 to 800 nm, with a peak at 614 nm, indicating that DCN7T absorbs solar energy more effectively than P3HT, which absorbs photons in the range of 400-650 nm with a peak at 522 nm. In addition, it is important to note that a shoulder at 670 nm suggests a vibronic progression enforced by strong intermolecular interactions among the thiophene rings and the cyanovinyl-substituents in DCN7T molecule, 7,19 which is redshifted compare with that of P3HT ͑at 600 nm͒. It is obvious that the blend films of DCN7T/PCBM exhibit broader absorption spectra than that of the pure DCN7T due to the complementary absorption spectra between the DCN7T and PCBM, implying an effective solar photon harvest.…”
mentioning
confidence: 99%
“…23) was used as an electron blocking layer to reduce the injected dark current density from the IZO anode at a reverse bias. [12][13][14] The molecular structures and energy levels of DMQA 24 and DCV3T 25 are depicted in Fig. 1(b).…”
mentioning
confidence: 99%